Strategi Wali Kelas Dalam Meningkatkan Disiplin Belajar Siswa Kelas II MIS Mathlaul Anwar 06 Pasir Nangka Cigudeg Bogor - Evi Lestari; Aal Jalaludin; Abudzar Al-Ghifari (PT PUSTAKA CENDEKIA GROUP, 2025)
This research focuses on the critical role of homeroom teachers in promoting student discipline, particularly in the learning process, to achieve optimal educational outcomes. A qualitative approach with a descriptive method was employed in this study. The subjects included the homeroom teacher and students at MI Mathlaul Anwar 06 Pasir Nangka. Data collection techniques involved observation, interviews, and documentation, while data analysis was carried out through data reduction, presentation, and conclusion drawing. The findings indicate that the strategies used by homeroom teachers include setting a positive example, consistently enforcing classroom rules, providing motivation, and applying persuasive methods or educational sanctions. Supporting factors for these strategies include cooperation with parents, collaboration with other teachers, and a conducive school environment. In contrast, inhibiting factors include students' lack of awareness regarding the importance of discipline and differences in family backgrounds. As a result, students' learning discipline improved, evidenced by better attendance, adherence to school rules, and increased engagement in lessons. This study underscores the vital role of homeroom teachers in fostering student learning discipline at the elementary school level.